Pencegahan Stunting melalui Penanganan Material Pangan dan Pengelolaan Keuangan Rumah Tangga - Vikaliana, Resista; Mariam, Siti; Aryani, Fika; Hidayat, Yusup Rachmat; Hermawan, Eric; Irwansyah (Forum Kerjasama Pendidikan Tinggi, 2024)
The aim of this activity is to increase the understanding of mothers who are members of Posyandu in RW 1 Kayumanis Village, Bogor City. The extension method was decided to be the method for this activity, with socialization activities as the activity that started the extension activities, then mentoring was carried out. This community service activity takes place from January to July 2023, with activity stages: Stage 1 (January 2023): Socialization of activities through RW Management and PKK Posyandu Cadres, Stage 2 (February 2023): Stunting education to PKK Posyandu Cadres, Stage 3 (March-May 2023): Prevention Assistance Stunting through Handling Food Materials and Managing Household Finances in Posyandu RW Activities (distribution of brochures and advice regarding the contents of the brochures), Stage 4 (June - July 2023): Evaluation of Activities through interviews and questionnaires. This community service activity has been able to increase understanding of mothers Posyandu members in RW 1 Kayumanis Village, Bogor City. This is indicated by the results of the questionnaire after the activity, in addition, interviews before and after the activity was carried out. Henceforth, it is recommended to provide assistance to the implementation of the socialization material provided, as well as the area coverage of the activities carried out.